Tire rubber powder composite toughened cast nylon and preparation method thereof

By using long-chain polyoxyethylene wrapped and grafted isocyanate tire glue powder in nylon materials, the problem of poor filler dispersion is solved, significantly improving the mechanical properties of cast nylon, which is suitable for large-scale production.

CN119410138APending Publication Date: 2025-02-11JIANGSU LVYUAN RUBBER RESOURCE RECYCLING INNOVATION CENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411553593.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The poor dispersion of fillers in existing nylon materials leads to limited improvement in mechanical properties, especially in crystalline polymers with large polarity differences.

Method used

By wrapping the tire glue powder with long-chain polyoxyethylene, grafting isocyanate groups on its surface, using the cocatalytic action of isocyanate, performing anion in situ polymerization reaction, and introducing the modified glue powder into the cast nylon system , thereby preparing tire glue powder composite toughened cast nylon.

Benefits of technology

It improves the dispersion and compatibility of rubber powder in the nylon matrix, improves the impact strength and elongation of break of cast nylon, while maintaining its tensile strength, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410138A_ABST
    Figure CN119410138A_ABST
Patent Text Reader

Abstract

The invention discloses tire rubber powder composite toughened cast nylon and a preparation method thereof, which are characterized in that long-chain polyoxyethylene is utilized to wrap tire rubber powder, isocyanate groups are grafted on the surface of the rubber powder by utilizing the reactivity of hydroxyl of polyoxyethylene and isocyanate, and the composite toughened cast nylon is prepared by utilizing the assistant catalysis effect of isocyanate. The modified rubber powder is introduced into a cast nylon system through an anion in-situ polymerization reaction, so that the modified rubber powder participates in the polymerization reaction to prepare the tire rubber powder composite toughened cast nylon composite material. On one hand, the polyoxyethylene-isocyanate organically modifies the surface of the tire rubber powder, so that the problems of dispersion and compatibility of the rubber powder in a nylon matrix can be solved, and the toughening effect of the rubber powder is more favorably exerted; and on the other hand, the long-chain polyoxyethylene has high lubricating property, and can effectively play a synergistic toughening role on the cast nylon by wrapping the surface of the rubber powder with the long-chain polyoxyethylene. The preparation method is simple and convenient, the toughening effect is obvious, meanwhile, high-value utilization of the tire rubber powder is achieved, and the tire rubber powder can serve as a structural material to be applied to the engineering field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer material synthesis and processing, and in particular relates to a method for preparing tire rubber powder composite toughened cast nylon. Background Art

[0002] Cast nylon, also known as monomer casting nylon or MC nylon (Monomer Casting Nylon), is formed by ring-opening polymerization of caprolactam monomer under the action of a catalyst. As a new technology and new material, it has gradually shown its unique advantages in many fields. Cast nylon has the characteristics of large molecular weight, high strength, good wear resistance and self-lubrication, which makes it widely used in mechanical equipment, chemical industry, high-temperature equipment and other fields. Its molding method is simple and the process conditions are easy to control, which further promotes its application in actual production. In addition, with the deepening of research, the performance of cast nylon has been continuously optimized and its application fields have been continuously expanded. At present, cast nylon has become an important engineering plastic and plays an important role in many fields.

[0003] With the rapid expansion of the rubber industry, the environmental problems caused by waste rubber have become increasingly prominent, and there is an urgent need to explore new ways to efficiently utilize it. Waste rubber can be made into waste rubber powder (WRP) that can be recycled for secondary use through methods such as extrusion regeneration, room temperature crushing, and low temperature freezing. As an elastic powder rubber material, it has a stable three-dimensional network structure inside, and because of its low cost and many excellent properties, it has shown broad application prospects in industries such as transportation and chemical industry, providing a new idea for solving the problem of waste rubber treatment.

[0004] In order to adapt polymers to more stringent conditions of use, people modify and reinforce polymers by adding other substances to improve and enhance the various properties of polymer materials. Chinese invention patent CN202010322049.4 discloses a toughened nylon material and its preparation method. By grafting toughening agent side chains on nylon monomers and diffusing to the interface to increase the intermolecular force, the elongation at break, impact strength and dimensional stability are effectively improved. Chinese invention patent CN202310113770.6 discloses a preparation method of glass fiber reinforced toughened nylon composite materials. By melt blending glass fiber with nylon resin, a nylon composite material with certain toughness is prepared. Although the above inventions have improved the toughness of nylon materials to a certain extent, since most of the fillers are non-crystalline polymers, and nylon is a crystalline polymer, the polarity of the two is quite different and the compatibility is poor, so the dispersion of fillers in nylon materials is poor, and the improvement of various mechanical properties of nylon is limited. Therefore, how to improve the dispersion of fillers in nylon materials to prepare toughened nylon composite materials with excellent performance still has a lot of research space. Summary of the invention

[0005] A tire rubber powder composite toughened cast nylon and a preparation method thereof are characterized in that the tire rubber powder is wrapped with long-chain polyoxyethylene, the reactivity of the hydroxyl group of polyoxyethylene with isocyanate is used to graft isocyanate groups on the surface of the rubber powder, and the modified rubber powder is introduced into the cast nylon system through anion in-situ polymerization reaction by using the catalytic effect of isocyanate, so as to participate in the polymerization reaction to prepare a tire rubber powder composite toughened cast nylon composite material. On the one hand, the organic modification of the tire rubber powder surface by polyoxyethylene-isocyanate can solve the dispersion and compatibility problems of the rubber powder in the nylon matrix, which is more conducive to the toughening effect of the rubber powder; on the other hand, the long-chain polyoxyethylene has high lubricity, and wrapping it on the surface of the rubber powder can effectively play a synergistic toughening effect on the cast nylon.

[0006] A tire rubber powder composite toughened cast nylon, the composite material mainly consists of the following components, calculated by mass:

[0007]

[0008] Wherein, the molecular weight of the polyoxyethylene is 6000-100000;

[0009] The catalyst is any one of sodium hydroxide, potassium hydroxide, sodium ethoxide, and sodium carbonate;

[0010] The co-catalyst is any one of toluene diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate;

[0011] A method for preparing tire rubber powder composite toughened cast nylon, the method comprising the following steps:

[0012] Tire rubber powder surface treatment

[0013] Dissolve 1-10 parts of polyoxyethylene powder in a certain amount of deionized water, ultrasonically disperse and stir for 1-5 hours to prepare a viscous polyoxyethylene aqueous solution with a concentration of 5%, then add 1-10 parts of tire rubber powder and stir at 70°C for 6-12 hours to fully swell the rubber powder, and then vacuum dry at a temperature of 60-85°C to constant weight; disperse the rubber powder treated with polyoxyethylene in 50-200 ml of N,N-dimethylformamide, add 2-20 parts of toluene diisocyanate thereto, ultrasonically disperse for 10-30 minutes, stir for 5 minutes, and vacuum dry at 60°C to obtain the surface-modified rubber powder;

[0014] Preparation of Tire Rubber Powder Composite Toughened Cast Nylon

[0015] 100 parts of caprolactam monomer are added to a three-necked flask, stirred and heated to 80°C, and evacuated after it is completely melted. At the same time, the temperature is raised to 125°C to remove moisture and low-boiling impurities therein. After removing the vacuum, the surface-modified rubber powder is added to the three-necked flask, stirred for 20-40 minutes, and then 0.05-8 parts of catalyst are added thereto. The reaction temperature is controlled at 130-140°C, and the vacuum is continued to be evacuated and stirred for 20 minutes. After removing the vacuum, 0.03-3 parts of co-catalyst are quickly added, and the mixture is quickly stirred evenly and poured into a stainless steel mold preheated to 165°C. The mold is placed in an oven at 165°C for 0.5-2h for anionic polymerization reaction, and the mold is taken out. After it is naturally cooled to room temperature, the mold is demolded to obtain tire rubber powder composite toughened cast nylon.

[0016] The invention has the following advantages: by synergistically modifying the rubber powder with polyoxyethylene and isocyanate, the problem of poor dispersion of the rubber powder due to the large difference in polarity between the rubber powder and the nylon material is solved. First, the surface of the rubber powder is coated with polyoxyethylene by means of adhesion, and then the reactivity of the hydroxyl group of polyoxyethylene with the isocyanate group is used to graft isocyanate on the surface of the rubber powder, so that the rubber powder is evenly distributed in the caprolactam monomer, and finally the cast nylon composite material is prepared by anionic ring-opening polymerization. The impact strength and elongation at break of the cast nylon are effectively improved by the rubber powder particles with a certain elasticity evenly distributed in the composite material, while maintaining its tensile strength. Compared with the commonly used melt blending method, the anionic polymerization method adopted by the invention also has the advantages of fast reaction speed, low reaction temperature, large product molecular weight, etc., and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 SEM image of the impact cross section of cast nylon toughened with tire rubber powder DETAILED DESCRIPTION

[0018] The present invention is further described below through specific embodiments. It should be noted that the embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make non-essential adjustments to the present invention based on the contents of the present invention described above.

[0019] Example 1

[0020] Dissolve 2 parts of polyoxyethylene powder with a molecular weight of 6000 in a certain amount of deionized water, ultrasonically disperse and stir for 1 hour to prepare a polyoxyethylene solution with a concentration of 5%, add 1 part of tire rubber powder to the prepared polyoxyethylene solution and stir at 70°C for 6 hours to make the rubber powder fully swell, then vacuum dry to constant weight at 80°C, disperse the polyoxyethylene treated rubber powder in 50ml N,N-dimethylformamide, add 2 parts of toluene diisocyanate thereto, ultrasonically disperse for 10 minutes, stir for 5 minutes, and vacuum dry at 60°C to obtain the surface-modified rubber powder.

[0021] 100 parts of caprolactam monomer were added to a three-necked flask, stirred and heated to 80°C, vacuumed after it was completely melted, and heated to 125°C to remove moisture and low-boiling impurities. After 20 minutes, the vacuum was removed, and the surface-modified rubber powder was added to the three-necked flask, stirred for 20 minutes, and then 0.05 parts of catalyst sodium hydroxide were added, and the reaction temperature was controlled at 130°C. The vacuum was continued and stirred for 20 minutes. After removing the vacuum, 0.03 parts of the co-catalyst toluene diisocyanate were quickly added, and the mixture was quickly stirred and poured into a stainless steel mold preheated to 165°C. The mold was placed in an oven at 165°C for 0.5h for anionic polymerization reaction, and the mold was removed. After it was naturally cooled to room temperature, the tire rubber powder composite toughened cast nylon was demoulded. After testing, its tensile strength was 75MPa, elongation at break was 69%, and impact strength was 4.25kJ / m 2 .

[0022] Example 2

[0023] Dissolve 5 parts of polyoxyethylene powder with a molecular weight of 20,000 in a certain amount of deionized water, ultrasonically disperse and stir for 2.5 hours to prepare a polyoxyethylene solution with a concentration of 5%, add 5 parts of tire rubber powder to the prepared polyoxyethylene solution and stir at 70°C for 9 hours to make the rubber powder fully swell, then vacuum dry to constant weight at 80°C, disperse the polyoxyethylene treated rubber powder in 100 ml of N,N-dimethylformamide, add 4 parts of toluene diisocyanate thereto, ultrasonically disperse for 10 minutes, stir for 5 minutes, and vacuum dry at 60°C to obtain the surface-modified rubber powder.

[0024] 100 parts of caprolactam monomer were added to a three-necked flask, stirred and heated to 80°C, vacuumed after it was completely melted, and heated to 125°C to remove the water and low-boiling impurities therein, and the vacuum was removed after 20 minutes, and the surface-modified rubber powder was added to the three-necked flask, stirred for 30 minutes, and then 0.5 parts of catalyst potassium hydroxide were added thereto, and the reaction temperature was controlled at 135°C, and the vacuum was continued to be drawn and stirred for 20 minutes. After removing the vacuum, 0.15 parts of the co-catalyst isophorone diisocyanate were quickly added, and the mixture was quickly stirred and poured into a stainless steel mold preheated to 165°C in advance, and the mold was placed in a 165°C oven for 1h for anionic polymerization reaction, and the mold was taken out, and after it was naturally cooled to room temperature, the tire rubber powder composite toughened cast nylon was demoulded. After testing, its tensile strength was 74MPa, the elongation at break was 94%, and the impact strength was 5.60kJ / m 2 .

[0025] Example 3

[0026] 10 parts of polyoxyethylene powder with a molecular weight of 6000 were dissolved in a certain amount of deionized water, ultrasonically dispersed and stirred for 5 hours to prepare a polyoxyethylene solution with a concentration of 5%, 10 parts of tire powder with a mesh size of 80 were added to the prepared polyoxyethylene solution and stirred at 70°C for 12 hours to make the rubber powder fully swell, and then vacuum dried at a temperature of 80°C to constant weight; the rubber powder treated with polyoxyethylene was dispersed in 150ml N,N-dimethylformamide, and 15 parts of toluene diisocyanate were added thereto, ultrasonically dispersed for 20 minutes, stirred for 5 minutes, and vacuum dried at 60°C to obtain the surface-modified rubber powder.

[0027] 100 parts of caprolactam monomer were added to a three-necked flask, stirred and heated to 80°C, vacuumed after it was completely melted, and heated to 125°C to remove the water and low-boiling impurities therein, and the vacuum was removed after 20 minutes, and the surface-modified rubber powder was added to the three-necked flask, stirred for 40 minutes, and then 4 parts of catalyst sodium ethoxide were added thereto, and the reaction temperature was controlled at 135°C, and the vacuum was continued to be drawn and stirred for 20 minutes. After removing the vacuum, 1 part of the co-catalyst hexamethylene diisocyanate was quickly added, and the mixture was quickly stirred and poured into a stainless steel mold preheated to 165°C, and the mold was placed in an oven at 165°C for 1.5 hours for anionic polymerization reaction, and the mold was removed, and after it was naturally cooled to room temperature, the tire rubber powder composite toughened cast nylon was demoulded. After testing, the tensile strength was 71MPa, the elongation at break was 112%, and the impact strength was 6.13kJ / m 2 .

[0028] Example 4

[0029] 10 parts of polyoxyethylene powder with a molecular weight of 100,000 were dissolved in a certain amount of deionized water, ultrasonically dispersed and stirred for 5 hours to prepare a polyoxyethylene solution with a concentration of 5%, 10 parts of tire rubber powder with a mesh size of 80 were added to the prepared polyoxyethylene solution and stirred at 70°C for 12 hours to make the rubber powder fully swell, and then vacuum dried at 80°C to constant weight; the rubber powder treated with polyoxyethylene was dispersed in 150ml N,N-dimethylformamide, and 10 parts of toluene diisocyanate were added thereto, ultrasonically dispersed for 30 minutes, stirred for 5 minutes, and vacuum dried at 60°C to obtain the surface-modified rubber powder.

[0030] 100 parts of caprolactam monomer were added to a three-necked flask, stirred and heated to 80°C, vacuumed after it was completely melted, and heated to 125°C to remove the water and low-boiling impurities therein. After 20 minutes, the vacuum was removed, and the surface-modified rubber powder was added to the three-necked flask, stirred for 40 minutes, and then 4 parts of catalyst sodium hydroxide were added thereto, and the reaction temperature was controlled at 140°C, and the vacuum was continued to be drawn and stirred for 20 minutes. After removing the vacuum, 2 parts of the co-catalyst toluene diisocyanate were quickly added, and after rapid stirring, it was poured into a stainless steel mold preheated to 165°C in advance, and the mold was placed in an oven at 165°C for 1.5 hours for anionic polymerization reaction, and the mold was taken out, and after it was naturally cooled to room temperature, the mold was demoulded to obtain tire rubber powder composite toughened cast nylon. After testing, its tensile strength was 67MPa, elongation at break was 136%, and impact strength was 6.69kJ / m 2 .

[0031] Example 5

[0032] Dissolve 5 parts of polyoxyethylene powder with a molecular weight of 6000 in a certain amount of deionized water, ultrasonically disperse and stir for 2.5 hours to prepare a polyoxyethylene solution with a concentration of 5%, add 3 parts of waste rubber powder with a mesh size of 80 to the prepared polyoxyethylene solution and stir at 70°C for 9 hours to make the rubber powder fully swell, and then vacuum dry to constant weight at a temperature of 80°C; disperse the polyoxyethylene treated rubber powder in 100 ml of N,N-dimethylformamide, add 6 parts of toluene diisocyanate thereto, ultrasonically disperse for 20 minutes, stir for 5 minutes, and vacuum dry at 60°C to obtain the surface-modified rubber powder.

[0033] 100 parts of caprolactam monomer were added to a three-necked flask, stirred and heated to 80°C, vacuumed after it was completely melted, and heated to 125°C to remove the water and low-boiling impurities therein, and the vacuum was removed after 20 minutes, and the surface-modified waste rubber powder was added to the three-necked flask, stirred for 30 minutes, and then 1 part of the catalyst sodium carbonate was added thereto, and the reaction temperature was controlled at 130°C, and the vacuum was continued to be drawn and stirred for 20 minutes. After removing the vacuum, 0.3 parts of the co-catalyst toluene diisocyanate were quickly added, and the mixture was quickly stirred and poured into a stainless steel mold preheated to 165°C in advance, and the mold was placed in a 165°C oven for 1h for anionic polymerization reaction, and the mold was taken out, and after it was naturally cooled to room temperature, the mold was demoulded to obtain tire rubber powder composite toughened cast nylon. After testing, its tensile strength was 75MPa, elongation at break was 88%, and impact strength was 5.2kJ / m 2 .

[0034] In summary, after the synergistic modification of the rubber powder by polyoxyethylene and isocyanate, the embodiment of the present invention successfully added waste rubber powder to the cast nylon system, improved the toughness of the cast nylon material, and successfully prepared cast nylon with good toughening effect, which can be used in the engineering field.

[0035] The above embodiments describe the specific contents of the present invention in detail, but the present invention is not limited to the embodiments, and those skilled in the art can make equivalent substitutions, which should be included in the protection scope of the present invention.

Claims

1. A tire rubber powder composite toughened cast nylon, characterized in that The main raw materials of the composite material are composed of the following components, calculated by weight: Wherein, the molecular weight of the polyoxyethylene is 6000-100000; The catalyst is any one of sodium hydroxide, potassium hydroxide, sodium ethoxide, and sodium carbonate; The co-catalyst is any one of toluene diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.

2. A method for preparing tire rubber powder composite toughened cast nylon as claimed in claim 1, characterized in that The method comprises the following steps: Tire rubber powder surface treatment Dissolve 1-10 parts of polyoxyethylene powder in a certain amount of deionized water, ultrasonically disperse and stir for 1-5 hours to prepare a viscous polyoxyethylene aqueous solution with a concentration of 5%, then add 1-10 parts of tire rubber powder and stir at 70°C for 6-12 hours to fully swell the rubber powder, and then vacuum dry at a temperature of 60-85°C to constant weight; disperse the rubber powder treated with polyoxyethylene in 50-200 ml of N,N-dimethylformamide, add 2-20 parts of toluene diisocyanate thereto, ultrasonically disperse for 10-30 minutes, stir for 5 minutes, and vacuum dry at 60°C to obtain the surface-modified rubber powder; Preparation of Tire Rubber Powder Composite Toughened Cast Nylon 100 parts of caprolactam monomer are added to a three-necked flask, stirred and heated to 80°C, and evacuated after it is completely melted. At the same time, the temperature is raised to 125°C to remove moisture and low-boiling impurities therein. After removing the vacuum, the surface-modified rubber powder is added to the three-necked flask, stirred for 20-40 minutes, and then 0.05-8 parts of catalyst are added thereto. The reaction temperature is controlled at 130-140°C, and the vacuum is continued to be evacuated and stirred for 20 minutes. After removing the vacuum, 0.03-3 parts of co-catalyst are quickly added, and the mixture is quickly stirred evenly and poured into a stainless steel mold preheated to 165°C. The mold is placed in an oven at 165°C for 0.5-2h for anionic polymerization reaction, and the mold is taken out. After it is naturally cooled to room temperature, the mold is demolded to obtain tire rubber powder composite toughened cast nylon.

Citation Information

Patent Citations

  • Toughened nylon material and preparation method thereof

    CN111471298A

  • Preparation method of glass fiber reinforced and toughened nylon composite material

    CN116200026A